Unique morphological characteristics in the ovary of cotton rat (Sigmodon hispidus) - Md. Rashedul ISLAM; Osamu ICHII; Teppei NAKAMURA; Takao IRIE; Md. Abdul MASUM; Marina HOSOTANI; Yuki OTANI; Yaser Hosny Ali ELEWA; Yasuhiro KON (The Society for Reproduction and Development, 2020)
Cotton rats (Sigmodon hispidus, CRs) are commonly used as animal models in biomedical research. However, the reproductive characteristics and ovarian development in the CRs has not been widely investigated. We have previously shown that female CRs, in particular, show several unique phenotypes associated with the urogenital system, such as chronic kidney disease and pyometra. Our investigation revealed unique morphologies in CR ovaries, particularly in oocytes. Cotton rat ovaries at 6-8 weeks of age were obtained from the Hokkaido Institute of Public Health, and their sections analyzed by light microscopy and transmission electron microscopy. Although the general histology and folliculogenesis of CR ovaries were similar to those of other experimental rodents, multi-oocyte follicles (MOFs) and double nucleated oocytes (DNOs) were also observed. Although MOFs were found at all stages of follicular development, a greater frequency of MOFs was observed in the primary and secondary stages. However, DNOs tended to be frequently observed in primordial follicles. Almost all MOF oocytes and a few DNOs possessed a clear zona pellucida, expressed DEAD (Asp-Glu-Ala-Asp) box polypeptide 4 and Forkhead box protein 2, a representative marker of oocytes and follicular epithelial cells. Thus, our investigations revealed the unique phenotypes of the CR ovary. As MOFs and DNOs are occasionally observed in human patients with infertility, the CR would be a useful animal model to study for gaining a better understanding of folliculogenesis and oocytogenesis, as well as their abnormalities in humans and other animals.